THE INTEGRATION OF SPIRITUAL VALUES IN COUNSELING INTERVETIONS TO REDUCE BULLYING BEHAVIOR - Wardhana, Andika Kusuma; Sutoyo, Anwar; Muslikah, Muslikah (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2025)
Ellison’s theory of spiritual well-being emphasizes that an individual’s well-being is not solely dependent on physical and psychological aspects, but also on the spiritual dimension that provides meaning in life and emotional balance. In the context of education, the implementation of spiritual well-being through spiritual guidance and counseling services can serve as an effective strategy to address bullying behavior. Spiritual guidance and counseling not only focus on resolving students’ psychological problems, but also instill transcendental values such as empathy, compassion, and respect for others. This research employs a descriptive qualitative method with a literature review approach to analyze the concept of spiritual guidance and counseling and its relevance in addressing bullying in schools. The findings indicate that the integration of spiritual values in guidance and counseling can foster students’ character development, making them more tolerant, appreciative of diversity, and morally aware. Furthermore, the application of spiritual guidance and counseling based on the principles of religious pluralism enables students to understand universal values that reject all forms of violence. Thus, spiritual guidance and counseling play a significant role not only in enhancing students’ holistic well-being, but also in creating a harmonious school environment free from bullying